Mandatory audit of small business in Malaysia. - Ismail, Hashanah; Loh , Lee Boon (University Putra Malaysia Press, 2012)
The study examines the views of owners and managers of small businesses in Serdang and Pudu to gauge their perceived usefulness of the annual statutory audit. The study finds that those in the city are more likely to perceive the audit as beneficial compared to owners of family owned light industry business.